Recent innovative results on natural fibre composites. (13th August 2009) - Vazquez, Analia; Stocchi, Ariel; Bernal, Celina
A novel fibre treatment recently proposed in the literature was optimised in the case of woven jute fabric/vinylester laminates to obtain the best tensile properties. It consists on an alkali treatment superimposed to biaxial tensile stress. Optimisation was performed by changing the treatment time. The novel fibre treatment was compared with traditional chemical methods. Tensile properties exhibited a maximum with the treatment time at 4 h due to the less efficient period of time and to the excessive fibre damage for times shorter and longer than 4 h, respectively. All composites with fibres treated with alkali under stress exhibited improved tensile strength in comparison with the composites with untreated fibres or with fibres treated with traditional methods due to the better interfacial properties and the structural changes of the fibres promoted by the novel treatment. Stiffness values were only higher for the composite with fibres treated with alkali under stress for 4 h, probably in correspondence with a maximum in the stiffness of the individual fibres.